(untitled) (Czech Journal of International Relations, 2003)
The year 1989 rendered a significant change for Denmark. For more than one century the country had to pursue a very passive foreign policy and its position was determined first by Germany (after the defeat in the Prussian- Austrian War in 1864) and later by the USSR (during the Cold War). The end of the Cold War brought about a new impulse for Copenhagen. From being a consumer of security during the Cold war, Denmark transformed to a producer of European security to a certain extent. Thanks to their determination, peace-keeping engagement and the interest in promotion of democracy and human rights, the Danes have gained a respected position in the world society. Denmark has also started supporting the European post-communist countries in their effort to join the NATO and the EU. It was only possible to pursue an activist foreign policy after 1989 when there was no direct threat to Denmark any longer. The international activism is the only means for small states, such as Denmark, to become more visible on the international political scene. The Danish membership in the EU has complicated this activist policy in a very specific way. Denmark has an opt-out from the Maastricht Treaty in the military aspects of the CFSP. Along with three other areas of European integration from which Denmark has opted out, the above mentioned reservation presents a paradox as it hinders the country from participating in peace-keeping operations only because they are taking place under the EU-command. To a certain degree, this opt-out paralyses the Danish international activism. As far as one can understand the other reservations concerning the common European currency, European citizenship (it is mainly symbolic in these cases) or the opt out from JHA, the defence opt-out complicates the Danish position significantly.